Incidência e causa de near miss materno: estudo de base populacional - Freitas, Cijara Leonice de (2020)
Objective: This study aimed to estimate the incidence and factors associated with maternal “near-miss”. Methods: A population-based study was carried out at reference maternity for obstetric and neonatal care of high complexity to women attended exclusively by the public health service. Data were collected from all pregnant women in labor who gave birth or in labor who gave birth or had complications within 42 days after delivery, admitted to the Maternity Hospital. The comparison between socio-demographic and health-related variables for maternal near-miss (MNM) cases and Severe Maternal Complications (SMC) were performed with Pearson chi-square (X2) for categorical and the Mann – Whitney test for continuous of socio-demographic and health-related. Results: A total of 568 women were identified as Maternal Near-Miss (MNM) case, and 2172 had Severe Maternal Complications (SMC). Thus, the total population was composed of 2740 cases.The maternal nearmissincidenceof 144.1 casesper 1000 live births (95% CI: 13.3 - 15.6) and an incidence among high-risk research pregnancies of 20.7% (95% CI: 19.2 - 22.2). Conclusions: low numbers of prenatal consultations, longer hospitalization time and requirement for intensive care unit were associated conditions for the development of maternalnear-miss.